Can village funds reduce the poverty rate in Kalimantan? - Zaen, Natasya Savitri; Andika Ridha Ayu Perdana (Economics, Finance, and Business Review, 2025)
Village funds have been rolled out by the government since 2015. The purpose of this study is to analyze the effect of village funds on poverty on the island of Kalimantan. In addition, this study investigated whether village funds were very effective in reducing poverty rates during the COVID-19 pandemic on the island of Kalimantan. This study examined all 47 districts that received village funds in the 2015-2022 period. The analysis method used is panel data regression. The results show that village funds have a negative effect on poverty on the island of Kalimantan. This finding indicates that village funds can reduce poverty rates on the island of Kalimantan. More importantly, the interaction between the village fund and COVID-19 variables has a negative sign. This finding implies that village funds are very effective in reducing poverty rates during the COVID-19 pandemic. In addition to village funds, high economic growth can reduce poverty rates on the island of Kalimantan. This finding implies that the government must continue to increase village funds and carry out good monitoring so that village funds can effectively reduce poverty rates in the regions.